Eduard Gans’ Hegelianism and the Verein für Cultur und Wissenschaft des Judentums: Reconsideration of a constellation regarding Heinrich Heine’s relationship to Hegel - Scherübl, Florian (Revista Eletrônica Estudos Hegelianos, 2020)
When Heinrich Heine entered the Berlin based Verein für Cultur und Wissenschaft des Judentums in 1822 this club´s aim was to achieve and anticipate a greater merging of Jewish and European culture, both thought of as separated around that time. Thanks to the philosophical input of Eduard Gans, the Verein´s project was founded on a Hegelian understanding of history and culture. Until today this early Hegelian influence in the Verein hasn´t been considered, at least not when it comes to the estimation of Heine´s relationship to Hegel. Neither were the problems that Heine seemed to have with some of his friend´s Hegelian notions. This paper seeks to explore the Hegelian background of the Verein in the light of[A1] Eduard Gans´ philosophical mediation and tries to highlight some aspects that point out towards an ongoing conflict between Hegelianism and Judaism throughout Heine´s work.